Os Jesuitas e A Monita Secreta - Rodrigues, Francisco (Tipographia Pontificia no Instituto Pio IX, 1912)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃